Associations between alcohol use and homelessness with healthcare utilization among human immunodeficiency virus-infected veterans. - Gordon, Adam J; McGinnis, Kathleen A; Conigliaro, Joseph; Rodriguez-Barradas, Maria C; Rabeneck, Linda; Justice, Amy C (Medical care, 2006)
Alcohol use is a frequent root cause of homelessness, and both homelessness and alcohol use influence the quality and quantity of interactions with health care providers.
Keywords: Adult; Alcohol Drinking; Female; Health Services; HIV Seropositivity; Homeless Persons; Humans; Male; Middle Aged; Questionnaires; Self Disclosure; Veterans